The First Amendment Lives On Conversations Commemorating Hugh M. Hefner's Legacy of Enduring Free Speech and Free Press Values - Brotman, Stuart N. (Book collections on Project MUSE., 2022)
"The format of the book is an homage to the in-depth conversational interviews Hefner pioneered as the editor and publisher of Playboy magazine. Stuart Brotman conducted in-person interviews with eight persons who in their lifetimes have come to represent a "greatest generation" of free speech and free press scholars and advocates"--